PFM.37 Cyclic tensile strain increases PGE2 release leading to weakening of the human term amniotic membrane. (9th June 2014) - Chowdhury, B; David, AL; Bader, DL; Thrasivoulou, C; Becker, D; Chowdhury, T
Abstract : Introduction: Uterine contractions, blood and infection may weaken the amniotic membrane (AM) leading to loss in biomechanical properties mediated by PGE2 release. We investigated AM mechanical properties and the effect of cyclic tensile strain (CTS) on PGE2 release and tissue composition in term AM. Methods: AM from the cervix ( C AM) and placental regions ( P AM) from elective term Caesarean section births were stained with India ink to identify fibre orientation either parallel ( II ) or perpendicular ( ⟂ C ) to the direction of applied strain and specimens strained to failure to calculate Tangent Modulus (TM). In separate experiments, dumb-bell shaped specimens underwent CTS (2%) and were analysed for collagen, elastin, GAG and PGE2 release. Results: Mechanical properties were dependent on fibre orientation with greater TM values for C AM/ P AM II compared to C AM/ P AM ⟂ (all p < 0.001). Values for TM were highest for P AM II (7.5MPa) vs C AM II (4.9 MPa; p < 0.01). In C AM II and P AM II, CTS significantly increased PGE2 values when compared to unstrained control samples (all p < 0.001). This led to augmented GAG synthesis and reduced collagen and elastin content when compared to controls (Figure ). Conclusion: CTS of the AM mimicking labour increased PGE2 release that reduced tissue composition leading to membrane softening. AM biomechanical properties are influenced by fibre orientation with relation to the direction of strain.